2022
DOI: 10.3390/su14137807
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Analysis of Enterprise Green Innovation and Green Financing in Platform Supply Chain

Abstract: In view of the financing dilemma of green innovation of manufacturers in the e-commerce supply chain, we build a strategy evolution game model between manufacturers and e-commerce platforms and describe the dynamic evolution law of manufacturers choosing green innovation and platforms choosing green financing. Combined with numerical simulation, the factors affecting green innovation and green financing decisions are analyzed and strategic suggestions are put forward. The conclusions are as follows: (1) There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The research of Yang, Y. X and others also confirmed that the type of local environmental regulations had a significant influence on the effectiveness of environmental policies [18]. Liu, L considered the particularity of the e-commerce industry and believed that whether the relevant enterprises could gain benefits through green finance depended on a variety of factors, such as additional income from innovation [19]. Yang, S. L and others found that the attitude of enterprises toward green finance depended not only on themselves but also on other enterprises [20].…”
Section: Literature On Green Financementioning
confidence: 84%
“…The research of Yang, Y. X and others also confirmed that the type of local environmental regulations had a significant influence on the effectiveness of environmental policies [18]. Liu, L considered the particularity of the e-commerce industry and believed that whether the relevant enterprises could gain benefits through green finance depended on a variety of factors, such as additional income from innovation [19]. Yang, S. L and others found that the attitude of enterprises toward green finance depended not only on themselves but also on other enterprises [20].…”
Section: Literature On Green Financementioning
confidence: 84%
“…Consequently, the two participants in the BFM exhibit a level of sustainability and adaptability, rather than being static entities. Through a process of trial and error, they continually modify their strategies in response to evolving circumstances, striving to achieve optimal results and ultimately attain a state of dynamic equilibrium [27,28]. As a result, this paper utilizes dynamic game theory to investigate and analyze the optimal strategies in the game played between the Chinese government and the private sector, which is consistent with the principles of dynamic game theory.…”
Section: Introductionmentioning
confidence: 89%
“…Li Xiaoli and Cheng Shuo introduce the network effect of e-commerce platforms into the cooperation process of the supply chain finance business, pointing out that e-commerce platforms will choose the cooperation strategy at a lower level of revenue sharing, and banks do not need supervision to realize complementary advantages and the rational allocation of resources [ 7 ]. Liu, L., Peng, Q. point out that when the amount of financing that the e-commerce platform needs to provide is too high, the platform will refuse green financing, and when the amount of financing is low, it is more likely to realize financing [ 8 ]. Xiaoyu Wang and Fasheng Xu examine the value of smart contracts in trade financing [ 9 ].…”
Section: Methodsmentioning
confidence: 99%